Atlantic meridional overturning circulation and the prediction of North Atlantic sea surface temperature - Kloewer, Milan; Latif, Mojib; Ding, Hui; Greatbatch, Richard John; Park, Wonsun (Earth and Planetary Science Letters, 2014)
Highlights: • North Atlantic sea surface temperature exhibits high decadal predictability potential. • Model bias hinders exploiting the decadal predictability potential. • An innovative method was developed to overcome some of the bias problem. • North Atlantic sea surface temperature will stay anomalously warm until about 2030. Abstract: The Atlantic Meridional Overturning Circulation (AMOC), a major current system in the Atlantic Ocean, is thought to be an important driver of climate variability, both regionally and globally and on a large range of time scales from decadal to centennial and even longer. Measurements to monitor the AMOC strength have only started in 2004, which is too short to investigate its link to long-term climate variability. Here the surface heat flux-driven part of the AMOC during 1900–2010 is reconstructed from the history of the North Atlantic Oscillation, the most energetic mode of internal atmospheric variability in the Atlantic sector. The decadal variations of the AMOC obtained in that way are shown to precede the observed decadal variations in basin-wide North Atlantic sea surface temperature (SST), known as the Atlantic Multidecadal Oscillation (AMO) which strongly impacts societally important quantities such as Atlantic hurricane activity and Sahel rainfall. The future evolution of the AMO is forecast using the AMOC reconstructed up to 2010. The present warm phase of the AMO is predicted to continue until the end of the next decade, but with a negative tendency.